Thermal study and characterization of new cocrystals of ciprofloxacin with picolinic acid - Torquetti, Carolina [UNESP] (2021)
This article describes the mechanochemical synthesis (liquid-assisted grinding (LAG) and neat grinding (NG)), characterization and thermoanalytical study of new cocrystals of ciprofloxacin (CIP) with picolinic acid (PCA) in a 1:1 molar ratio. Characterization was performed through thermoanalytical techniques (differential scanning calorimetry (DSC), simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC)), X-ray powder diffraction (XRPD) and infrared spectroscopy (IR). The thermoanalytical study, together with the XRPD and IR techniques, confirmed the formation of new cocrystal and helped to understand its formation. From the LAG method, using ethanol as a solvent, a cocrystal solvate was obtained. The NG method, together with thermal stress, favored obtaining the cocrystal through a coamorphous intermediate phase. Solubility study of all new materials showed an increase in CIP concentration for the cocrystals compared to pure drug.